2005
DOI: 10.1002/eat.20077
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial correlates, outcome, and stability of abnormal adolescent eating behavior in community samples of young people

Abstract: Abnormal eating behavior in adolescence and young adulthood is clearly associated with various indicators of psychosocial maladaption. In adolescence, it does not significantly predict any psychiatric disorder including eating disorder in young adulthood and it is predominantly a transient feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 23 publications
7
50
0
1
Order By: Relevance
“…3,7 Specifically, our study shows that the period of greatest risk for females is mid-adolescence. This finding is in accordance with prior studies reporting this age group as peak risk for bulimic behaviors 8,10,35 : Stice et al 10 found 17-to18-year-old females at greatest risk for the onset of bulimia and binge eating, and Calam and Waller 35 reported a higher level of bulimic symptoms at 19 years than at 12 years. Unlike the aforementioned studies, however, this study specifically explores the trend of bulimic pathology in females from a developmental perspective, following a large number of participants through important stages of their early development to young adulthood.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…3,7 Specifically, our study shows that the period of greatest risk for females is mid-adolescence. This finding is in accordance with prior studies reporting this age group as peak risk for bulimic behaviors 8,10,35 : Stice et al 10 found 17-to18-year-old females at greatest risk for the onset of bulimia and binge eating, and Calam and Waller 35 reported a higher level of bulimic symptoms at 19 years than at 12 years. Unlike the aforementioned studies, however, this study specifically explores the trend of bulimic pathology in females from a developmental perspective, following a large number of participants through important stages of their early development to young adulthood.…”
Section: Discussionsupporting
confidence: 91%
“…3,6 In general, adolescence is considered the critical developmental stage for bulimic symptoms, and the symptoms increase during this period. 3,7 The peak risk for abnormal eating behavior seems to be mid-adolescence (15-16 years), 8 while binge eating and purging appear somewhat later. 9 A recent community-based longitudinal study also reported that the peak period of risk for onset of bulimia and binge eating was between ages 17 and 18.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal studies investigating the course of disordered eating from adolescence to young adulthood in the community are limited in number and have yielded heterogeneous results, most likely due to relatively small sample sizes, different study designs or selection of patients. Whilst several recent studies have demonstrated that ED and eating-disordered behaviour are stable from early adolescence to young adulthood [9][10][11], other previous studies did not find evidence of continuity of this behaviour in the majority of subjects [12,13]. In the majority of studies, continued eating-disordered behaviour was accompanied by a wide range of psychopathology and the development of obesity [11,12,14].…”
Section: Introductionmentioning
confidence: 92%
“…Whilst several recent studies have demonstrated that ED and eating-disordered behaviour are stable from early adolescence to young adulthood [9][10][11], other previous studies did not find evidence of continuity of this behaviour in the majority of subjects [12,13]. In the majority of studies, continued eating-disordered behaviour was accompanied by a wide range of psychopathology and the development of obesity [11,12,14]. In a recent prospective study of males and females followed from 14 to 20 years of age by Allen et al [15], all ED diagnoses at all time points were associated with depressive symptoms and poor mental health quality of life.…”
Section: Introductionmentioning
confidence: 96%
“…Disordered eating behaviors and attitudes appear to be quite common in childhood and adolescence, [5][6][7][8][9] and are associated with a host of negative health consequences [10][11][12][13][14][15][16] as well as an increased risk for the development of a full-syndrome ED. [17][18][19][20][21] In particular, overweight youth are significantly more likely than their non-overweight peers to report body dissatisfaction, 22,23 binge eating, 7,24 and the use of unhealthy weight control methods, 23,25,26 and overweight in childhood has been identified as a specific risk factor for bulimia nervosa (BN) and binge eating disorder (BED).…”
Section: Introductionmentioning
confidence: 99%